2018
DOI: 10.1088/1361-648x/aaf0ef
|View full text |Cite
|
Sign up to set email alerts
|

Structural, elastic and vibrational properties of celestite, SrSO4, from synchrotron x-ray diffraction, thermal diffuse scattering and Raman scattering

Abstract: In order to resolve inconsistencies encountered in published data for SrSO4, the elasticity and the phase stability of celestite has been studied using thermal diffuse scattering, high pressure powder synchrotron X-ray diffraction, Raman scattering and DFT calculations. The structure of SrSO4 is found to be stable up to 62 GPa at ambient temperature. The preferred values for the components of the elastic stiffness tensor have been determined using X-ray thermal diffuse scattering and are (in GPa): c11 = 105, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
(78 reference statements)
1
14
0
1
Order By: Relevance
“…At temperatures above 450 • C, the peak becomes slightly asymmetric in shape and is more accurately fitted by a mixed Gaussian and Lorentzian curve (Figure 4). Although this splitting is not apparent at room temperature, Kloprogge et al [35] reported the splitting of the ν 1 band of celestine at 77 K and Girard et al [36] reported the appearance of a shoulder on the low wavenumber side of celestine with increasing pressure. The ν 3 bands of barite all show a systematic decrease in wavenumber with increasing temperature with the 1138 cm −1 band exhibiting a non-linear temperature dependence (Table 3).…”
Section: Barite Temperature Dependencementioning
confidence: 99%
“…At temperatures above 450 • C, the peak becomes slightly asymmetric in shape and is more accurately fitted by a mixed Gaussian and Lorentzian curve (Figure 4). Although this splitting is not apparent at room temperature, Kloprogge et al [35] reported the splitting of the ν 1 band of celestine at 77 K and Girard et al [36] reported the appearance of a shoulder on the low wavenumber side of celestine with increasing pressure. The ν 3 bands of barite all show a systematic decrease in wavenumber with increasing temperature with the 1138 cm −1 band exhibiting a non-linear temperature dependence (Table 3).…”
Section: Barite Temperature Dependencementioning
confidence: 99%
“…Ambient temperature is a good starting point, and 265 and 235 K can be easily reached by employing a nitrogen jet. The choice of a ÁT of 30 K was based on previous studies (Wehinger et al, 2017;Girard et al, 2019) where it was used successfully.…”
Section: Methodsmentioning
confidence: 99%
“…Further mathematical background is provided by e.g. Wehinger (2013), Wehinger et al (2017) or Girard et al (2019). We fitted the TDS data using the open-source package TDS2EL2 with the multitemperature approach (Wehinger et al, 2017).…”
Section: Determination Of C Ijmentioning
confidence: 99%
See 2 more Smart Citations